Method for Predicting Barge Impact Force Based on Nonlinear Spring Stiffness - Junhu Shao; Yulin Zhan; Shuai Song; Mengqi Cai; Xiaoping Chen; Haiying Yu (Shock and Vibration)
Accurate prediction of barge impact force contributes greatly to the research of the soundness of the bridge under barge impact. Toward this end, the calculation method of barge impact force caused by ship-bridge collision is investigated in this study. Firstly, a comparative analysis for different energy conversion relationships is conducted via the high-precision finite element method (HPFEM) and the coupled vessel impact analysis (CVIA). A construction method of nonlinear spring stiffness (NSS) is proposed therefrom. Secondly, a high-precision finite element model is developed to simulate the barge-bridge collision under different barge masses and impact velocities. NSS under each condition is obtained, and the influences of barge mass and impact velocity on NSS are further discussed. An NSS model considering the effects of impact mass and impact velocity is proposed. Lastly, based on the NSS model, a prediction method of barge impact force is introduced. The results show that the impact mass has little influence on the peak value of NSS; however, the impact mass and impact velocity have a great influence on the tail of the NSS curve. According to the characteristics of NSS, four key control points can be extracted and NSS is simplified into a polyline model. The NSS model of the barge is obtained by nonlinear response surface fitting. The impact force can be predicted by combining the simplified NSS model and the proposed method in this study. The proposed method in this paper does not consider the pier stiffness; hence, it can be combined with NSS to quickly estimate the impact force, which can provide a design basis for the impact force in ship-bridge collision design. The rigid wall and a continuous rigid frame bridge impacted by the barge are studied; the results show that the proposed method can reasonably estimate the impact force.